Prognostic Value and Risk Factors of Treatment-Related Lymphopenia in Malignant Glioma Patients Treated With Chemoradiotherapy: A Systematic Review and Meta-Analysis - Zhang, Yongchao; Chen, Shichao; Chen, Hualei; Chen, Shanshan; Li, Zhen; Feng, Enshan; Li, Wei (Frontiers in Neurology, 2022)
Background: Immunotherapy have showed promising therapeutic efficacy on various cancers, but not on glioma yet. Circulating lymphocytes play critical roles in cancer control and response to immune checkpoint inhibitors. Patients with treatment-related lymphopenia has been associated with worse survival in various tumors. This meta-analysis was conducted to evaluate risk and impact of lymphopenia in glioma patients. Methods: A comprehensive search of the PubMed, Embase, Web of science and Cochrane library was performed and eligible studies selected if they reported the incidence and risk factors of lymphopenia and the impact of lymphopenia on survival. Stata 16.0 was used for this meta-analysis. Results: A total of 21 studies were included in the final systematic review and twenty in the quantitative analysis. Overall incidence of III/IV lymphopenia was 31.6% (95% CI: 22.3% -40.8%). Pooled results showed that the patients with severe lymphopenia were associated with poor overall survival (hazard ratio [HR] = 1.99, 95% CI: 1.74-2.27, P<0.001) compared to patients with no severe lymphopenia. Brain receiving radiation dose 20 Gy or 25 Gy were predictive of lymphopenia, while being female, older age, lower baseline lymphocyte counts, and dexamethasone dose greater than 2 mg instead of baseline use were other risk factors. Conclusions: Treatment-related lymphopenia is associated with decreased survival in glioma. Optimization of the chemoradiation regimens, particularly in patients with concurrent other risk factors can reduce lymphopenia and potentially improve survival in the era of immunotherapy.